Reduction of Polycyclic Aromatic Hydrocarbons (PAHs) in Sesame Oil Using Cellulosic Aerogel - Do-Yeong Kim; Boram Kim; Han-Seung Shin (Foods, 2021)
The effect of cellulosic aerogel treatments used for adsorption of four polycyclic aromatic hydrocarbons (PAHs)—benzo[a]anthracene, chrysene, benzo[b]fluoranthene, and benzo[a]pyrene [BaP]—generated during the manufacture of sesame oil was evaluated. In this study, eulalia (Miscanthus sinensis var. purpurascens)-based cellulosic aerogel (adsorbent) was prepared and used high performance liquid chromatography with fluorescence detection for determination of PAHs in sesame oil. In addition, changes in the sesame oil quality parameters (acid value, peroxide value, color, and fatty acid composition) following cellulosic aerogel treatment were also evaluated. The four PAHs and their total levels decreased in sesame oil samples roasted under different conditions (p < 0.05) following treatment with cellulosic aerogel. In particular, highly carcinogenic BaP was not detected after treatment with cellulosic aerogel. Moreover, there were no noticeable quality changes in the quality parameters between treated and control samples. It was concluded that eulalia-based cellulosic aerogel proved suitable for the reduction of PAHs from sesame oil and can be used as an eco-friendly adsorbent.